Why companies choose to lease instead of buy? : Insights from academic literature - Morais, Ana (2022)
Purpose – The purpose of this paper is to review empirical research on the determinants of leasing. Design/methodology/approach – The paper reviews previous literature that has focused on studying the determinants of leasing decisions. It also discusses the determinants of the lease-buy decision and the determinants of the choice between finance leases and operating leases. Findings – Previous empirical studies show that there is no consensus as to whether debt and leases are complements or substitutes. However, there are some factors that affect the choice between leases and debt, such as size, taxes, nature of assets, financial constraints and management compensation. Leases tend to be more prevalent in some industries (such as air transport, retailing and services and utilities) than in others, and companies tend to lease assets that are less specific, of general usage and more liquid. Previous studies also show that higher leverage companies tend to use leases rather than other forms of financing. Research limitations/implications – The paper only addresses the determinants of leasing. Previous studies about leases address other areas such as the lease accounting standards and the economic consequences and valuation of leases, which are not discussed in this paper. Originality/value – The paper presents an exhaustive review of previous literature on the determinants of leasing. Evidence from research on this topic is likely to be helpful in capital market investment decisions, accounting standard setting and decisions on corporate financial disclosure.